Data alchemy in the insurance industry : the transformative power of big data analytics - Taneja, Sanjay; Kumar, Pawan; Reepu; Kukreti, Mohit; Özen, Ercan (Emerald Publishing Limited, 2024)
Data Alchemy in the Insurance Industry: The Transformative Power of Big Data Analytics is a groundbreaking work that explores the transformative power of big data analytics within the insurance industry. This collected edition takes readers on a journey into the world of data-driven alchemy, where insurers turn vast amounts of information into valuable insights and innovations. By demystifying the complex realm of big data, Data Alchemy empowers insurance researchers and professionals to harness data effectively, create efficiencies, and achieve a competitive edge. This collected edition provides a comprehensive and practical roadmap for insurers, data scientists, technologists, and insurance enthusiasts alike, to navigate the data-driven revolution that is sweeping the insurance landscape. Authors in this work offer a series of case studies featuring renowned insurance companies that have successfully harnessed data analytics for strategic gains. They discuss not only the technological facets but also regulatory concerns, ethical considerations, and the human element in data-driven insurance transformation. This work anticipates the future trends and challenges that will shape the insurance industry, providing insights into how data alchemy will continue to evolve and impact the sector. This collected edition is essential reading for data scientists, technologists, researchers in the field of big data analytics, as well as insurers who implement research findings.